Isotropic Broadband E-Field Probe - Béla Szentpáli; István Réti; Ferenc B. Molnár; János Farkasvölgyi; Károly Kazi; Zoltán Mirk; Aurél Sonkoly; Zoltán Horváth (Active and Passive Electronic Components)
An E-field probe has been developed for EMC immunity tests performed in closed space. The leads are flexible resistive transmission lines. Their influence on the field distribution is negligible. The probe has an isotropic reception from 100 MHz to 18 GHz; the sensitivity is in the 3 V/m–10 V/m range. The device is an accessory of the EMC test chamber. The readout of the field magnitude is carried out by personal computer, which fulfils also the required corrections of the raw data.